Multiwell study of seismic attenuation at the CO2CRC Otway project geosequestration site: Comparison of amplitude decay, centroid frequency shift and 1D waveform inversion methods. (26th May 2019) - Pirogova, A.; Pevzner, R.; Gurevich, B.; Glubokovskikh, S.; Tertyshnikov, K.
ABSTRACT: At the CO2CRC Otway geosequestration site, the abundance of borehole seismic and logging data provides a unique opportunity to compare techniques of Q (measure of attenuation) estimation and validate their reliability. Specifically, we test conventional time‐domain amplitude decay and spectral‐domain centroid frequency shift methods versus the 1D waveform inversion constrained by well logs on a set of zero‐offset vertical seismic profiles. The amplitude decay and centroid frequency shift methods of Q estimation assume that a seismic pulse propagates in a homogeneous medium and ignore the interference of the propagating wave with short‐period multiples. The waveform inversion explicitly models multiple scattering and interference on a stack of thin layers using high‐resolution data from sonic and density logs. This allows for stable Q estimation in small depth windows (in this study, 150 m), and separation of the frequency‐dependent layer‐induced scattering from intrinsic absorption. Besides, the inversion takes into account band‐limited nature of seismic data, and thus, it is less dependent on the operating frequency bandwidth than on the other methods. However, all considered methods of Q estimation are unreliable in the intervals where subsurface significantly deviates from 1D geometry. At the Otway site, the attenuation estimates are distorted by sub‐vertical faults close to the boreholes. Analysis of repeated vertical seismic profiles reveals that 15 kt injection of the CO2 ‐rich fluid into a thin saline aquifer at 1.5 km depth does not induce detectable absorption of P‐waves at generated frequencies 5–150 Hz, most likely because the CO2 plume in the monitoring well is thin, <15 m. At the Otway research site, strong attenuation Q ≈ 30–50 is observed only in shaly formations (Skull Creek Mudstone, Belfast Mudstone). Layer‐induced scattering attenuation is negligible except for a few intervals, namely 500–650 m from the surface, and near the injection interval, at around 1400–1550 m, where Q scat ≈ 50–65.